Degloving Approach for the Management of Extensive Mandibular Osteomyelitis. Issue 3 (May 2021) - Shadamarshan R, Arunkumar; Sharma, Rohit; Grewal, Ritu
Abstract : Abstract: Extensive osteomyelitis of the mandible is usually managed using elaborate procedures including resection and reconstruction of the affected part of the mandible. This brief clinical report, the authors present a case of 75-year old male with extensive osteomyelitis of the mandible, incidentally diagnosed with anemia of chronic disease and Type I diabetes mellitus and managed using an intraoral degloving approach exclusively. This has proved to be a procedure ensuring better blood supply, decreased morbidity, precluding an elaborate reconstruction procedure and an overall reduction in cost. The advantages, scientific basis, rationale and pitfalls have been discussed briefly.